A Critical Review and Analysis of Construction Equipment Emission Factors. (2017) - Fan, H.
Abstract: Diesel-powered construction equipment is the primary source of Green House Gas (GHG) and exhaust emissions during the construction stage of a large infrastructure project. The equipment pollutants such as nitrogen oxides, carbon monoxide, and particulate matter (PM 2.5 and PM 10) endanger people's health and surrounding environment. A critical review and analysis of factors affecting the amounts of construction emissions is conducted through literature review and a case study, four categories of factors including equipment and conditions, equipment maintenance, operating conditions, and equipment operations are reviewed. A case study is made on 14 wheel loaders with different makes and capacities with accumulated weekly data with the aim of determining the impact of emission factors on the weekly equipment emissions. It is found that equipment engine power, equipment conditions, and equipment operator skills are significant factors on average fuel consumption and emissions in the case study. Based on the findings from current research literature and the case study, some recommendations are made on how to reduce fuel consumptions as well as pollutant emissions for contractors and other equipment owning organizations.